2023
DOI: 10.3390/foods12061253
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Allergenicity: An Insight into Its Mitigation Using Thermomechanical Processing

Abstract: Peanuts are the seeds of a legume crop grown for nuts and oil production. Peanut allergy has gained significant attention as a public health issue due to its increasing prevalence, high rate of sensitization, severity of the corresponding allergic symptoms, cross-reactivity with other food allergens, and lifelong persistence. Given the importance of peanuts in several sectors, and taking into consideration the criticality of their high allergic potential, strategies aiming at mitigating their allergenicity are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
(188 reference statements)
1
3
0
Order By: Relevance
“…The IC 50 of RPE, boiled peanut extract, roasted peanut-1 extract, roasted peanut-2 extract, and fried peanut extract were observed at dilution factors of 6462.21 (2.82 μg/mL protein), 914.47 (2.97 μg/mL protein), 1776.33 (2.43 μg/mL protein), 1734.93 (2.31 μg/mL protein), and 1270.52 (6.04 μg/mL protein), respectively. These findings indicate that roasting enhances human IgE-immunoreactivity of peanut, while boiling/frying reduces it, which is consistent with the findings on Ara h 2 IgE-immunoreactivity described above and to those of previous reports ( 40 , 44 , 45 ), suggesting that Ara h 2 could serve as a useful biomarker for predicting IgE-binding changes of peanut. The IC 50 of beverage-1, beverage-2, and cookie were observed at dilution factors of 802.81, 4497.0, and 69.84 respectively, indicating that the IgE-binding ability of peanut in these sample extracts was different.…”
Section: Resultssupporting
confidence: 92%
“…The IC 50 of RPE, boiled peanut extract, roasted peanut-1 extract, roasted peanut-2 extract, and fried peanut extract were observed at dilution factors of 6462.21 (2.82 μg/mL protein), 914.47 (2.97 μg/mL protein), 1776.33 (2.43 μg/mL protein), 1734.93 (2.31 μg/mL protein), and 1270.52 (6.04 μg/mL protein), respectively. These findings indicate that roasting enhances human IgE-immunoreactivity of peanut, while boiling/frying reduces it, which is consistent with the findings on Ara h 2 IgE-immunoreactivity described above and to those of previous reports ( 40 , 44 , 45 ), suggesting that Ara h 2 could serve as a useful biomarker for predicting IgE-binding changes of peanut. The IC 50 of beverage-1, beverage-2, and cookie were observed at dilution factors of 802.81, 4497.0, and 69.84 respectively, indicating that the IgE-binding ability of peanut in these sample extracts was different.…”
Section: Resultssupporting
confidence: 92%
“…Scientific reports revealed that, in France, approximately 15% of food-related anaphylaxis in the pediatric population is caused by legumes, and among them, the most common trigger is peanuts, which are responsible for almost 80% of cases. The determination of the prevalence and relevance of sensitization to legumes in peanut-allergic children is needed because of the increasing consumption of legumes, data on cross-reactivity between peanuts and other legumes, and frequent severe allergic reactions observed in children with a peanut allergy [65,66].…”
Section: Peanut-induced Anaphylaxis and Component-resolved Diagnosticmentioning
confidence: 99%
“…Another problem connected with peanut utilization is its high allergenic potential, either consumed by itself or in combination with other foods or allergens where cross-reactions can occur. A recently published review paper by Haidar et al [76] offers several technological solutions to reduce allergenicity of peanuts, which include processing at high temperatures (e.g., boiling, baking, frying) or the use of ultrasound and high pressure (autoclaving).…”
Section: Mung Beansmentioning
confidence: 99%